A novel algorithm for modeling and mapping of 3D terrain in autonomous reconnaissance - Billah, Md. Masum; Khan, Md. Raisuddin; Ahmed, Mohiuddin (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2012)
A new algorithm for undertaking three-dimensional (3D) terrain mapping in autonomous reconnaissance has been presented in this paper. The novel algorithm generates 3D discrete terrain data that is acquired from terrain surface using inertial sensors. The algorithm uses fractal interpolation to generate 3D terrain surface. This algorithm can be implemented in reconnaissance mission for building 3D map unknown surfaces without using light.